Analisa Pengaruh Brand Image, Brand Trust, Dan Brand Ambassador Terhadap Minat Beli Pada Platformm Digital Shopee (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Nurzakiah Ahmad; Mohammad Rizal; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study pursuits to decide the analysis impact of brand image, brand trust, brand ambassador on the purchase intention of platform digital shopee (a case take in  Economics and Business students, Islamic University of Malang). The method used in quantitativ data types. The technique utilized in descriptive studies evaluation with quantitative records. The pattern in this examine found 75 respondents. With the method used on this look at purposive sampling. The impact confirmed that Brand image, Brand trust, and Brand ambassador have a significant  impact on  purchase intention. Brand image have a significant impact on Purchase intention. Brand trust have a significant impact on Purchase intention. Brand ambassador have a significant impact on Purchase intention.  Keywords: Brand Image, Brand Trust, Brand Ambassador And Purchase Intention.